Efektivitas Pengelolaan Sentra Industri Hasil Peternakan Di Kecamatan Sinjai Selatan Kabupaten Sinjai - Ikbal; Hermansyah; Fitrawati AB (Universitas Mbojo Bima, 2025)
The purpose of this study is to determine the , Effectiveness of livestock industry Center management ini south sinjai district, sinjai regency and the dterminant factors for livestock industri center management in saouth sinjai district, sinjai regency, as well as to clarify the problem formulation taken by the author. This study uses a qualitative approach. The data obtained are analyzed based on indicators the have been determinad through obsevation. Interviews and documentation from research informants. Primary data were obtained from in depth interviews with the head of the UPTD livestock industry center, the head of the industry and IKM section.The results of the study on the Effectiveness of the Management of the Livestock Product Industry Center in South Sinjai District, Sinjai Regency, show that in the production aspect, the Livestock Product Industry Center is not yet effective because of the 20 IKM. that are members, only 3 IKM. carry out regular production so that the production house is often not utilized so that there is no production target. From the aspect of packing, the processed products made by IKM have quite good packing but are not yet effective because they use modern packaging and tools, but the packaging does not have BPOM and halal label. From the market aspect, the Livestock Product Industry Center is not yet effective because marketing only focuses on local sales. In terms of contribution, the Livestock Product Industry Center is effective because there are no levies charged to IKM. The supporting factors for the success of the Livestock Product Industry Center are market access and government support while the challenges faced are limited capital and for IKM and management of the UPTD Livestock Product Industry Center and IKM.This research was conducted at the UPTD Livestock Product Industry Center in South Sinjai District, Sinjai Regency and the Department of Trade, Industry, and Mineral Resources of Sinjai Regency. Keywords: Effectiveness, Management, Industrial Centers, IKM